NICCOLÒ MACHIAVELLI‘S POLITICAL PHILOSOPHY IN SHAKESPEARE‘S RICHARD III - Vlajnić, NIkola (Political Review, 2024)
William Shakespeare provides readers with an insight into his understanding of power and politics through writing historical plays set in the period of English history known as the Wars of the Roses. Niccolò Machiavelli explicitly expresses his understanding of politics in his most famous work The Prince. In this paper, we tried to identify the relationship between the political thought of the two authors through a comparative analysis of Shakespeare's historical play Richard III and Machiavelli's The Prince. We have concluded that there are several similarities between Shakespeare‘s and Machiavelli‘s understanding of politics. We identified a complementarity in their views of human nature, the means for coming to power, and the dangers that can lead to overthrowing. However, we also noticed important differences primarily concerned with understanding the relationship between politics and morals.
Keywords: William Shakespeare; Niccolò Machiavelli; Richard III; The Prince; usurpation of power; Machiavellianism; morals in politics